"Tell them what they want to hear and get back to work": Insights into the utility of current occupational health assessments from the perspectives of train drivers. (December 2018) - Naweed, Anjum; Chapman, Janine; Trigg, Joshua
Graphical abstract: Highlights: Periodic health assessments for train drivers are mandatory to monitor health risk. Focus group data show that assessments engender perceptions of division and threat. Industry response to driver health is reactive: long-term, sustainable change is needed. A systems approach, committed to open culture and participatory intervention is required. Topic remains strategic rail research priority and socioeconomic objective for policy makers. Abstract: Australian train drivers undergo periodic health assessments as part of a nationally standardised approach to reducing sudden incapacitation risk, given the demonstrated potential for occupational and public harm. These assessments occur pre-placement, then every 5 years to age 50, then every 2 years to age 60, and then every year. Despite some reported benefits to rail workforce health indicators since implementation, research suggests the assessments are not operating as effectively as they might. For example, the prevalence of obesity in drivers is higher than in the general population and continues to increase. To improve this, there is a need to understand the experiences of drivers undergoing workplace health assessments. The aims of this study were to examine train drivers' perceptions and experiences of the assessments, understand how these experiences shape their engagement with the process, and to generate recommendations for improvement from a systems thinking perspective. A qualitative design was used, involving semi-structured interviews within five focus groups of train drivers ( n  = 29) held across four Australian rail organisations. Questions addressed drivers' backgrounds, their understanding of the National Standard, experiences of and attitudes towards health assessments, lifestyle risk factors, and personal approach to health and wellbeing. Transcript data were subjected to thematic analysis. Five factors were identified: drivers' unmet information needs, perceived low reliability and validity of assessment, need for psychological wellbeing assessment and support, maladaptive threat avoidance strategies, and focus on short-term outcomes and compliance. The global theme was reactive organisational culture. Findings suggest that driver engagement with health assessment can be improved by proactively addressing the identified factors in occupational health initiatives and preventative interventions to tackle the burgeoning problem of train driver health impairment.